Hepatocyte growth factor combined with adenosine deaminase as biomarker for diagnosis of tuberculous pleural effusion - Zheng, Sheng-Cai; Huang, Zhong-Yin; Zhai, Kan; Shi, Huan-Zhong; Shao, Ming-Ming (Frontiers in Microbiology, 2023)
The simple, rapid, and accurate diagnosis of tuberculous pleural effusion (TPE) remains difficult. This study aimed to determine the accuracy of hepatocyte growth factor (HGF) in the diagnosis of TPE.Methods: We quantified the expression of HGF, adenosine deaminase (ADA), and interferon gamma (IFN-γ) in pleural effusion (PE) in 97 TPE subjects and 116 non-TPE subjects using an enzyme-linked immunosorbent assay (ELISA) or a fully automatic biochemical analyzer. The diagnostic performance of these three biomarkers was evaluated using a receiver operating characteristic (ROC) curve of subjects by age and gender.Results: We discovered that the TPE group had much higher levels of HGF than the non-TPE group, regardless of age or gender, and that there was no statistically significant difference between the two groups' levels of HGF expression in peripheral plasma. In female TPE patients aged ≤65 years, the AUCs of TPE and non-TPE diagnosed by HGF, ADA or IFN-γ were 0.988,0.964 and 0.827, respectively. HGF plus ADA had the highest diagnostic efficacy in female TPE patients aged ≤65 years. With HGF plus ADA having a cut-off value of 0.219 for distinguishing TPE from non-TPE, the area under the curve (AUC), sensitivity (SEN), specificity (SPE), positive predictive value (PPV), and negative predictive value (NPV) were respectively 0.998 (95% confidence interval [CI], 0.993-1.000), 100 (95% CI, 89.997-100.000), 96.667 (95% CI, 82.783-99.916), 97.222 (95% CI, 83.594-99.586), and 100.This study confirmed that HGF plus ADA has high diagnostic efficacy in younger female TPE patients and has the potential to be an excellent biomarker.